Contribution of Symbiotic Fungi to Cork Oak Colonization by Platypus cylindrus (Coleoptera: Platypodidae) - Inácio,Maria Lurdes (2011)
Platypus cylindrus Fab. (Coleoptera: Platypodidae) has changed its status from uncommon to pest contributing to cork oak decline. Besides its massive attacks, P. cylindrus is associated with fungi on which it depends for survival and host colonization. Isolations from beetles yielded seven genera with a potential role on insects' establishment: Acremonium, Biscogniauxia, Botryosphaeria, Gliocladium, Raffaelea, Scytalidium and Trichoderma. Raffaelea spp. were the most frequent fungi (ambrosia fungi) mainly in insect’s mycangia and gut confirming their role as primary symbionts and possibly capable of weaken the host. Similarly Biscogniauxia and Botryosphaeria genera may act to overwhelm tree defenses. The genera Scytalidium, Gliocladium andTrichoderma are known to have a degradative wood ability and play a pioneering role in host colonization. These results demonstrate the close association between P. cylindrus and its ambrosia fungi. These are mainly from the Raffaelea genus and also the auxiliary ambrosia fungi, whose presence is part of the insect's strategy for host colonization.